Two artists and two mélodies: André Caplet and Charles Baudelaire. Issue 3 (1st December 2021) - Wilson, Clare
Abstract : André Caplet (1878–1925) set just two of Baudelaire's poems: La Cloche fêlée ['The Cracked Bell'] and La Mort des pauvres ['The Death of the Poor']. These mélodies were composed in 1922, just three years before the artist's death. For a composer with a tendency to shy away from setting poetry of the French giants of literature, the questions of how and why Caplet chose to translate Baudelaire's poetry into the mélodie are intriguing. This exploration of La Cloche fêlée and La Mort des pauvres considers the ways in which Caplet reflects the poetic imagery of Baudelaire's texts within musical structures. Caplet's compositional language is distinctive, and his artistic approach to musically illuminating poetic meaning is perceptive and sensitive. Through viewing the creative intersection of these two artists, this article offers an interpretation that presents a perspective on Caplet's musical character and reveals insight into his connection to Baudelaire's poetic language.